PENGARUH KOMPETENSI, SISTEM INFORMASI AKUNTANSI DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KINERJA UMKM KOTA BATAM - Ayani, Nia; Banjarnahor, Haposan (SCIENTIA JOURNAL, 2024)
Micro, Small and Medium Enterprises (MSMEs) are a business that is able to help the economic growth of the Indonesian state where these MSMEs are able to open jobs and this will reduce poverty and aggregation. The purpose of this study is to determine whether Competence, Accounting Information Systems and Information Technology Utilization affect the Performance of MSMEs in Batam City. The data source used is from primary data through questionnaire distribution. The data analysis technique used in the study is to analyze multiple liner regrenances with the ordinary least square method, but because heterokedacity occurs, researchers use the estimates parameter with robust standard errors as a benchmark in determining significance. The results of the research show that HR Competence and Accounting Information Systems have a significant effect on MSME performance, while the use of information technology does not affect MSME performance. This research is expected to provide a more comprehensive understanding of the importance of improving MSME performance in Batam.